Protein Level Defense Responses of Theobroma cacao Interaction With Phytophthora palmivora - Rego, Angra Paula Bomfim; Mora-Ocampo, Irma Yuliana; Pirovani, Carlos Priminho; Luz, Edna Dora Martins Newman; Corrêa, Ronan Xavier (Frontiers in Agronomy, 2022)
Species of the genus Phytophthora cause black-pod rot, which is the disease responsible for the largest losses in cocoa production in the world. The species Phytophthora palmivora affects cacao tree cultivation in all producing countries. However, proteomic level studies of the Theobroma cacao-P. palmivora interaction remains unpublished. Thus, the aim of this study was to analyze this pathosystem through comparative proteomics and systems biology analyses. The proteins were extracted from leaves of T. cacao PA 150 (resistant) and SIC 23 (susceptible) clones 48 h after inoculation with P. palmivora using inoculation with sterile distilled water as controls. There were differences in the protein profile between the control and inoculated treatments of both clones. Thirty-seven distinct proteins were identified on 88 spots of the PA 150 treatments, and 39 distinct proteins were identified on 120 spots of the SIC 23 treatments. The metabolisms of ATP, carbohydrates and nitrogen compounds had higher percentages of proteins with increased accumulation after inoculation in both clones. Systems biology analysis demonstrated that the networks contain a higher number of proteins in the clusters corresponding to processes of photosynthesis and glucose metabolism, suggesting that they are the most affected by the infection. In addition, lipoxygenase, 2-methylene-furan-3-one reductase-like, and co-chaperonin CPN20 proteins and a probable CC NBS LRR protein may be involved in resistance to black-pod disease caused by P. palmivora.